Proszę o szybkie rozwiązanie .. Oblicz. : [latex] frac{4}{7} [/latex] - [latex] frac{1}{3} [/latex] = [latex] 6frac{5}{12} [/latex] - [latex] 4frac{5}{6} [/latex] = [latex] 4frac{2}{7} [/latex] - [latex] 2frac{}{} [/latex] = [latex] 3frac{1}{3}

Proszę o szybkie rozwiązanie .. Oblicz. : [latex] frac{4}{7} [/latex] - [latex] frac{1}{3} [/latex] = [latex] 6frac{5}{12} [/latex] - [latex] 4frac{5}{6} [/latex] = [latex] 4frac{2}{7} [/latex] - [latex] 2frac{}{} [/latex] = [latex] 3frac{1}{3} [/latex] - [latex] frac{2}{5} [/latex] =
Odpowiedź

[latex]frac{4}{7}-frac{1}{3}=frac{12}{21}-frac{7}{21}=frac{5}{21}\6frac{5}{12}-4frac{5}{6}=6frac{5}{12}-4frac{10}{12}=5frac{17}{12}-4frac{10}{12}=1frac{7}{12}\4frac{2}{7}-2=2frac{2}{7}\3frac{1}{3}-frac{2}{5}=3frac{5}{15}-frac{6}{15}=2frac{20}{15}-frac{6}{15}=2frac{14}{15}\[/latex]

[latex]frac{4}{7}-frac{1}{3}= frac{12}{21}-frac{7}{21} =frac{5}{21} \ \ 6frac{5}{12} - 4frac{5}{6}= frac{77}{12} - frac{29}{6}= frac{77}{12}-frac{58}{12}=frac{19}{12} = 1frac{7}{12} \ \ 4frac{2}{7} - 2 = 2frac{2}{7} \ \ 3frac{1}{3}-frac{2}{5} = frac{10}{3}-frac{2}{5}= frac{50}{15}-frac{6}{15}= frac{44}{15}= 2frac{14}{15}[/latex]

Dodaj swoją odpowiedź